Evaluasi Proses Konsolidasi Tanah Kawasan Permukiman Kumuh Bantaran Sungai Kurau Klaster 1 Desa Kurau Berdasarkan Persepsi Masyarakat - Yurmansah, Yurmansah; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Settlement condition of the River Plate Kurau Cluster 1 Kurau slum village made arrangements with land readjustment, but in the implementation of the case back by the public rejection of the result of an agreement or a consensus that settlements be halted. Therefore, it is necessary to evaluate the land consolidation process in order to assess the success of land readjustment process and the factors that hamper implementation. This study uses a mix method with a two-stage procedure. Results of the analysis showed that the land land readjustment process successfully, supported by the success of the equity (score 638), effectiveness (score 631), responsiveness (score 617) and efficiency (579). The success of land land readjustment is caused by, among others, people's desire to stay or do not want to be relocated / displaced, not the status of land ownership society, high support and commitment of local governments and legislators. whereas the factors that hinder the implementation of the agreement of land land readjustment triggered by the inequity in the distribution of location / position of the lots after the land land readjustment of the small percentage of people, causing rejection back public the results of land land readjustment, among others, less efficient and less fair to the size distribution and financing schemes recovery.Â